Associations between sensitivity to antibiotics, disinfectants and heavy metals in natural, clinical and laboratory isolates of Escherichia coli. (25th March 2020) - Bischofberger, Anna M.; Baumgartner, Michael; Pfrunder‐Cardozo, Katia R.; Allen, Richard C.; Hall, Alex R.
Summary: Bacteria in nature often encounter non‐antibiotic antibacterials (NAAs), such as disinfectants and heavy metals, and they can evolve resistance via mechanisms that are also involved in antibiotic resistance. Understanding whether susceptibility to different types of antibacterials is non‐randomly associated across natural and clinical bacteria is therefore important for predicting the spread of resistance, yet there is no consensus about the extent of such associations or underlying mechanisms. We tested for associations between susceptibility phenotypes of 93 natural and clinical Escherichia coli isolates to various NAAs and antibiotics. Across all compound combinations, we detected a small number of non‐random associations, including a trio of positive associations among chloramphenicol, triclosan and benzalkonium chloride. We investigated genetic mechanisms that can explain such associations using genomic information, genetic knockouts and experimental evolution. This revealed some mutations that are selected for by experimental exposure to one compound and confer cross‐resistance to other compounds. Surprisingly, these interactions were asymmetric: selection for chloramphenicol resistance conferred cross‐resistance to triclosan and benzalkonium chloride, but selection for triclosan resistance did not confer cross‐resistance to other compounds. These results identify genetic changes involved in variable cross‐resistance across antibiotics and NAAs, potentially contributing to associations in natural and clinical bacteria.